Corrigendum: Study of water discharge in the Ulee Lheue Port Channel, Indonesia (IOP Conf. Ser.: Earth Environ. Sci. 429 012013). Issue 1 (January 2020) - Setiawan, I; Isbah, F; Muhammad, M; Yuni, S M; Purnawan, S; Akram, A; Ilhamsyah, Y
Abstract : Page 2: In the section 2., the following text appears: "2. Materials and metodhs" This should read: "2. Materials and methods" In the 2.2. Research procedure section, the following text appears: "This velocity measurement was held four times a day at the three depths, as presented in Figure 2." This should read: "This velocity measurement was held four times a day at the three depths, as presented in Figure 1." Page 3: In the 3.1. Water depth section, the following text appears: "The data concerning water depth from the week I to IV are presented in Figure 3 to 6." This should read: "The data concerning water depth from the week I to IV are presented in Figure 2 to 5." Page 5: In the 3.2. The current velocity section, the following text appears: "Figure 7 shows that is the current velocity of the 5th day at 03:00 pm was the highest in the first week, that was 0.26 m/s." "Based on Figure 8, the current velocity on 12th Jumada I at 09:00 am was 0.35 m/s because the depth of the water also headed towards the tide, resulting in the large current into the port channel." This should read: "Figure 6 shows that is the current velocity of the 5th day at 03:00 pm was the highest in the first week, that was 0.26 m/s." "Based on Figure 7, the current velocity on 12th Jumada I at 09:00 am was 0.35 m/s because the depth of the water also headed towards the tide, resulting in the large current into the port channel."